2017
DOI: 10.1007/s12350-016-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the safety, hemodynamic response, and diagnostic accuracy of commonly used vasodilator stressors in patients with severe aortic stenosis

Abstract: Severe AS patients are more likely to have a hemodynamically significant decrease in systolic BP with vasodilator stress. There were no serious adverse events in this severe AS cohort with good diagnostic performance of MPI compared to angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Exercise-induced myocardial ischemia may occur in these patients, even in the absence of CAD ( 35 41 ). While exercise-stress testing is contraindicated for symptomatic patients with severe AS, it has clinical relevance for identifying those asymptomatic AS-patients who are at high-risk of poor prognosis ( 8 , 9 , 35 41 ). Pharmacological stress tests such as single photon emission computed tomography (SPECT), positron emission tomography (PET) or cardiac magnetic resonance (CMR) with different vasodilators (adenosine, dipyridamole or regadenoson) have been shown to be a valuable alternative to exercise-stress testing for the CAD assessment in these patients ( 35 41 ).…”
Section: Coronary Artery Disease Assessment In Patients With Aortic S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise-induced myocardial ischemia may occur in these patients, even in the absence of CAD ( 35 41 ). While exercise-stress testing is contraindicated for symptomatic patients with severe AS, it has clinical relevance for identifying those asymptomatic AS-patients who are at high-risk of poor prognosis ( 8 , 9 , 35 41 ). Pharmacological stress tests such as single photon emission computed tomography (SPECT), positron emission tomography (PET) or cardiac magnetic resonance (CMR) with different vasodilators (adenosine, dipyridamole or regadenoson) have been shown to be a valuable alternative to exercise-stress testing for the CAD assessment in these patients ( 35 41 ).…”
Section: Coronary Artery Disease Assessment In Patients With Aortic S...mentioning
confidence: 99%
“…In patients with severe AS, the conventional exercise-stress test and thallium-201 exercise-scintigraphy are generally found to be inaccurate with low specificity for CAD assessment since clinical symptoms and baseline ECG abnormalities are neither specific nor sensitive (35)(36)(37)(38)(39)(40)(41). Exercise-induced myocardial ischemia may occur in these patients, even in the absence of CAD (35)(36)(37)(38)(39)(40)(41).…”
Section: Coronary Artery Disease Assessment In Patients With Aortic S...mentioning
confidence: 99%
See 1 more Smart Citation
“…First, myocardial perfusion SPECT analysis mainly relies on perfusion, which is also dependent on MVD, hence our additional separate analysis of patients with normal and high IMR. Nevertheless, a recent study showed a good diagnostic performance of SPECT in patients with severe AS (35). Furthermore, SPECT is readily available in our institutions for the quantification of myocardial ischemia, and additional imaging with the use of positron emission-computerized tomography or perfusion cardiac magnetic resonance imaging is not feasible due to availability and practical issues in our elderly study population.…”
Section: Limitationsmentioning
confidence: 94%
“…To fill the gap between evidence and practice, Hussain et al recently investigated the safety of vasodilator MPS in 95 patients (average age, 79 years) with severe aortic stenosis (mean aortic valve area, 0.79 cm 2 ). 8 They showed that dipyridamole, adenosine, and regadenoson had comparable safety profiles with no occurrence of major adverse events or serious complications. Although patients with valve disease were nearly twice as likely to experience a marked reduction ([20 mmHg) in systolic blood pressure as patients without disease, none experienced symptomatic hypotension.…”
mentioning
confidence: 99%